In silico modeling of acetylcholinesterase inhibition by caffeic acid derivatives (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Alzheimer’s disease (AD) is characterized by progressive neurodegeneration that primarily affects older adults worldwide. Although no cure currently exists, present therapies target key enzymes involved in AD pathophysiology, such as acetylcholinesterase (AChE), whose inhibition enhances cholinergic neurotransmission. Available drugs act via this mechanism but exhibit important limitations in efficacy and adverse effects. Therefore, this study aims to evaluate, in silico, the inhibition between caffeic acid (CA) derivatives and the AChE enzyme. To conduct this research, AutoDock Vina was used for molecular docking between AChE (PDB: 4MOE) and CA derivatives obtained from the PubChem database. The results showed interactions with amino acid residues critical for AChE inhibition. In conclusion, these findings provide a theoretical basis for subsequent in vitro and in vivo studies aimed at the design of mixed AChE inhibitors derived from phenolic compounds.